Determinan Keputusan Penggunaan Paylater pada Platform E-commerce (Studi Kasus Mahasiswa FEB Universitas Selamat Sri) - Eka Kurnia Patmasari; Ayu Akhiri Ana; Siti Abdillah Nurhidayah (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study is motivated by the irresponsible use of paylater services, which is influenced by factors such as financial literacy, risk perception, and trust. The purpose of this research is to examine the impact of financial literacy, risk perception, and trust on students’ decisions to use paylater services at the Faculty of Economics and Business, Selamat Sri University. A quantitative survey method was employed, targeting a sample of 107 students from the 2020 cohort who actively utilized paylater services. The findings reveal that financial literacy significantly and positively influences the use of paylater services. Similarly, risk perception and trust also exhibit significant positive effects on paylater usage.